Bilingual education in French-speaking sub-Saharan Africa : state of play and challenges to be met - (:unkn) unknown (My University, 2021)
For quite a long time, French-speaking sub-Saharan African countries have been trying to find effective strategies in order to use African languages as a teaching medium. One of these strategies consists in setting up an integrated "first language - French as second language" programme. The advantages of such a programme are no longer to be proven. Indeed, the benefits of introducing the first learning in the mother tongue are obvious, both in terms of the construction of the knowledge and skills of the student and in terms of identity. This is the reason why most of the Ministries of Education in French-speaking sub-Saharan Africa have embarked on projects to experiment with integrated teaching "National language - French", or even reform their national unilingual programs towards bi-plurilingual devices. However, in most of these countries, scaling up is problematic and unilingual curricula, inherited from colonial education heuristics, remain in the majority.At the end of 2020, research indicates that few French-speaking countries in sub-Saharan Africa have truly initiated a plan to deploy bi-plurilingual schooling. Several blockages have to be lifted.During our communication, we will develop these statements around 3 axes. First, we will present the results of PASEC, the Regional Program for the Analysis of Education Systems, and see how these results prove that French-speaking sub-Saharan Africa is currently in crisis.Secondly, we will analyze the main advantages of bilingual programmes, and explain how its scaling up would improve the quality of teaching / learning.Finally, in a third part, we will present the various challenges that remain to be taken up for a real consideration of the first languages of learners in the classrooms.
Keywords: African Research